A parameter design of CNC plasma-arc cutting of carbon steel plates using robust design. (1st September 2010) - Kechagias, John; Billis, Michael; Maropoulos, Stergios
An optimisation of the cutting parameters during CNC plasma-arc cutting of St37 mild steel plates is attempted using robust design. The process parameters tested were plate thickness, cutting speed, arc ampere, arc voltage, air pressure, pierce height, and torch standoff distance. An orthogonal matrix experiment [L18 (21 × 37) ] was conducted and the right bevel angle was measured and optimised according to the process parameters using an analysis of means and an analysis of variances. The results show that the arc ampere has an effect mainly on the bevel angle (50.89%), while the plate thickness and torch standoff distance also have an influence of 6.22 and 15.9% respectively. The other parameters have an F factor smaller than one, and thus their variations do not significantly affect the bevel angle in the experimental region. Finally, an additive model was applied on the experimental results to predict the optimum combination and was compared with actual values.